DETERMINING FACTORS OF THE PROCESS OF CO-EVOLUTION OF NATURE AND THE ETHNIC COMMUNITIES OF WESTERN CAPSUS IN THE EPOCH OF THE GREAT HUMAN MIGRATION - Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2016)
The article presents the range of factors, which had a decisive influence on the interaction of the landscape of the Western Caspian Sea Region and migrating tribes during the Migration Period. According to their priority they are classified into: a) natural; b) ethnocultural; c) environmental; d) political; d) war; e) ideological; f) military and strategic factors.